The Child-Friendly School Program for Developing a Character School in the Primary Schools of Binjai City, Indonesia - Indra Prasetia; Emilda Sulasmi; Susana Susana (RIRAI Publisher, 2021)
This research is a qualitative research in the form of a case study. This research is conducted at Binjai State Elementary School, Indonesia. The purpose of this study is to implement a child-friendly school program and develop student character programmed in the Primary Schools of Binjai Ciy, Indonesia. The respondents of this study are principals and teachers. The results of this study are child-friendly school policies at Primary Schools of Binjai City encourage all school residents to care about the school environment and be anti-violent so that the atmosphere at school becomes healthy, safe and comfortable. The formation of the character of students through child-friendly schools Primary Schools of Binjai City is going well because the teachers at the school have formed the character of students including students who are diligent and diligent in learning, respect for teachers, discipline, respect each other so as to form a community friendly study. Child-friendly school programs are very effective in forming a safe and conducive school environment and supporting the development of student character, in addition to encouraging schools to develop infrastructure to support learning. The study also found that some schools still have obstacles in developing a school culture for the direction of child-friendly schools. In general, Primary Schools of Binjai City has implemented child-friendly education, where the school has attempted various programs and activities in implementing child-friendly education.